Analysis of high-density current deposits in the Puente Formation (Arequipa Basin), Southern Peru - Jacay Huarache, Javier Pablo (2005)
The sedimentary Basins of the Jurassic half-superior of the Andes Power stations (Peru), with a rate of high sedimentation, they happened during a period of distension. The Arequipa Basin that was developed during the Jurassic one inferior to half, it presents characteristic morphological, sedimentológicas and tectonic that is typical of a «basin in distension.» One of these characteristics is the turbidityc filler those that present flows of graveness of exceptional thickness Megaturbidites, those that correspond to products of catastrophic events during the resedimentación.